ہندوستانی اقبال شناس سید مظفر حسین برنی بہ طور مدون: تنقیدی جائزہ - Dr. Muhammad Amir Iqbal; Namatullah Arshid Ghumaan; Dr. Mushtaq Adil (Khayaban - خیابان, 2023)
Apart from being a great poet, Iqbal was also a great thinker and intellectual. His letters are a source of thought and wisdom. Mr. Barni has collected Iqbal's letters with great effort. He has completed the task of editing the letters. Many points have been sorted out and detailed, explained and given arguments. By working with authentic references, Mr. Barni has edited the letters. There are some mistakes are coming up which are inviting new researchers to research. The study of this article will create openness in the field of Iqbaliyat. It will develop new ways of research and criticism and will lead to the creation of new topics.